Impact test strength analysis of composites reinforced with palm fiber (ijuk) - Muhammad Saddam Alghofur, Muhammad Saddam Alghofur; Husman, Husman; Erwanto, Erwanto (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2026)
The development of material technology drives the need for strong, lightweight, and environmentally friendly materials. One solution that is widely developed is natural fiber-based composite materials because they have good mechanical strength, abundant availability, and are biodegradable. Palm fiber (Arenga pinnata) is one of the potential candidates as a composite reinforcement due to its moisture-resistant, strong, and easily available properties in nature. This study aims to analyze the effect of variations in the volume fraction of palm fiber and the soaking time of 5% NaOH on the impact toughness of Yukalac 157 BQTN polyester resin-based composites. The method used is an experimental method with a hand lay-up process in making specimens and testing was carried out using a GOTECH GT-7045 impact testing machine according to ISO 179-1 standards. The variations tested include fiber volume fractions of 25% and 30% and soaking times of 2 hours and 3 hours. The results showed that the 25% fraction with a 2-hour immersion produced the highest toughness of 82.39 kJ/m², while the 30% fraction showed an increase in strength after a 3-hour immersion with a value of 37.77 kJ/m². This combination produces a polyester resin-based composite that is strong, lightweight, and has the potential to be used as an alternative material for sustainable motor vehicle body panels.